Lived experience of women from their life and their children's life after divorce - mahya yarigarravesh (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2022)
Divorce brings many harms. Separation of couples and the breakdown of marriage are accompanied by feelings of failure, distress, sadness, ambiguity and confusion in life, lifestyle changes and, most likely, psychological disorders. Women play a pivotal role in society. When a woman separates from her husband, many psychological and social harms are inflicted on her and their children. In the present study, the attitudes of divorced women toward the separation process, their lives and those of their children, and their future were studied qualitatively and phenomenologically. The study sample consisted of 15 women who had children and were separated from their husbands. The research tool was a semi-structured interview and thematic analysis method was used to analyze the information obtained from the research. After coding and analyzing the information obtained from the interviews with the participants of the four main themes, 12 sub-themes along with 97 concepts of information analysis were obtained. The results showed that problems before and during marriage are the most important factors in the separation and financial problems and the issue of meeting the father are among the other problems after the mother separates from the wife. Other information obtained from the present study is that using the advice of counselors to reduce post-divorce injuries is also beneficial for mother and child.